Strategi Komunikasi Pemasaran Terpadu Penjual Asli Papua Dalam Penjualan Pinang Lokal Di Pasar Remu Kota Sorong - Dwi Iin Kahinah; Masseni Masseni (Hikmah, 2025)
This study aims to examine the integrated marketing communication (IMC) strategies used by indigenous Papuan traders in marketing local areca nut (pinang) at Remu Market, Sorong City, Southwest Papua, Indonesia. The research responds to the issue of how traditional traders sustain their livelihoods through effective communication strategies within a competitive local market. A qualitative phenomenological approach was employed to explore the lived experiences of twelve indigenous traders (seven women and five men) who have been trading pinang for more than five years. Data were collected through semi-structured interviews, observation, and documentation, and analysed using thematic analysis to identify strategic communication patterns, supporting and inhibiting factors, and government involvement. The findings show that traders practice informal but cohesive IMC, emphasizing trust-based relationships, visual product display, and oral storytelling. Supporting factors include stable demand, cooperative supplier networks, and community endorsement. Conversely, challenges arise from inconsistent product quality, limited infrastructure, and restricted financial resources. Government involvement was found to be partial and inconsistent, with some training programs but weak follow-up. The study concludes that IMC among indigenous traders is deeply rooted in cultural values and community ties. Strengthening this system requires collaborative programs integrating communication training, infrastructure improvement, and financial empowerment to enhance market sustainability and preserve local identity